Pengaruh Komunikasi Pemasaran Terhadap Keputusan Pembelian Dengan Minat Beli Sebagai Variabel Intervening Pada Konsumen Cantika Beautycare Metro Lampung - Fitriani; Suwarto; Rini Aprina (Jurnal Manajemen DIVERSIFIKASI, 2025)
the author gives the title of this thesis "The influence of marketing communications on purchasing decisions with purchase interest as an intervening variable among consumers of Beautycare Metro Lampung" The main problem in the research is the fluctuation in the number of visitors to Cantika Beautycare Metro Lampung, however, to maintain its position as one of the superior beauty clinics, Cantika Beauycare must be able to implement the right marketing strategy. This research aims to examine the influence of marketing communications on purchasing decisions with purchase interest as an intervening variable for Cantika Beautycare Metro Lampung consumers. The variables used in this research are marketing communications as an independent variable, purchase interest as an intervening variable and purchasing decisions as a dependent variable. The data source in the research is primary data where the data collection method uses a questionnaire method distributed at Cantika Beautycare Lampung. The number of samples whose data were successfully processed was 50 respondents. The sample selection method used was the simple random sampling method. Where all populations have the same opportunity to be selected as samples. The data analysis technique used is path analysis. The results of hypothesis testing in this research show that marketing communication and purchasing interest have a positive and significant effect on purchasing decisions for Cantika BeautycareMetro Lampung products. And this The main problem in the research is the fluctuation in the number of visitors to Cantika Beautycare Metro Lampung, however, to maintain its position as one of the superior beauty clinics, Cantika Beauycare must be able to implement the right marketing strategy. This research aims to examine the influence of marketing communications on purchasing decisions with purchase interest as an intervening variable for Cantika Beautycare Metro Lampung consumers. The variables used in this research are marketing communications as an independent variable, purchase interest as an intervening variable and purchasing decisions as a dependent variable. The data source in the research is primary data where the data collection method uses a questionnaire method distributed at Cantika Beautycare Lampung. The number of samples whose data were successfully processed was 50 respondents. The sample selection method used was the simple random sampling method. Where all populations have the same opportunity to be selected as samples. The data analysis technique used is path analysis. The results of hypothesis testing in this research show that marketing communication and purchasing interest have a positive and significant effect on purchasing decisions for Cantika BeautycareMetro Lampung products. And this research also explains the direct influence of marketing communications on purchasing decisions and the indirect influence through purchasing interest (as an intervening variable), and the results have a positive and significant effect. Keywords: marketing communications, purchasing interest, and purchasing decisions.research also explains the direct influence of marketing communications on purchasing decisions and the indirect influence through purchasing interest (as an intervening variable), and the results have a positive and significant effect.